International business cycle accounting - Keisuke Otsu (University of Kent, School of Economics, 2010)
In this paper, I extend the business cycle accounting method a la Chari, Kehoe and McGrattan (2007) to a two-country international business cycle model and quantify the effect of the disturbances in relevant markets on the business cycle correlation between Japan and the US over the 1980-2008 period. I find that disturbances in the labor market and production efficiency are important in accounting for the recent increase in the cross-country output correlation. Financial globalization can be the cause of the recent increase in cross-country output correlation if it operated through an increase in the cross-country correlation of disturbances in the labor market and production efficiency, not in the domestic or international capital markets.
Keywords: E32; F41; 330; business cycle accounting; international business cycles; financial globalization